• Упростите выражение:
    ((b/a^2-ab)-(1/a-b)):((a+b/a^2-ab)-(b/ab-b^2))

    question img

Ответы 1

  • 1)  \frac{b}{ a^{2} -ab} - \frac{1}{a-b}= \frac{b-a}{a(a-b)} = -\frac{a-b}{a(a-b)} =- \frac{1}{a}  2)  \frac{a+b}{ a^{2} -ab}- \frac{b}{ab- b^{2} }= \frac{a+b}{a(a-b)}- \frac{b}{b(a-b)}= \frac{(a+b)b-ab}{ab(a-b)} = \frac{ab+ b^{2} -ab}{ab(a-b)} = \frac{b}{a(a-b)}      3) -\frac{1}{a}: \frac{b}{a(a-b)} =- \frac{1}{a}* \frac{a(a-b)}{b} = -\frac{a-b}{b} = \frac{b-a}{b}   Ответ:  \frac{b-a}{b}
    • Автор:

      ziggy42
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years